Outcomes based on age in the phase III METEOR trial of cabozantinib versus everolimus in patients with advanced renal cell carcinoma. (February 2020) - Donskov, Frede; Motzer, Robert J.; Voog, Eric; Hovey, Elizabeth; Grüllich, Carsten; Nott, Louise M.; Cuff, Katharine; Gil, Thierry; Jensen, Niels Viggo; Chevreau, Christine; Negrier, Sylvie; Depenbusch, Reinhard; et al.
Abstract: Background: Cabozantinib improved progression-free survival (PFS), overall survival (OS) and objective response rate (ORR) compared with everolimus in patients with advanced renal cell carcinoma (RCC) after prior antiangiogenic therapy in the phase III METEOR trial (NCT01865747). Limited data are available on the use of targeted therapies in older patients with advanced RCC. Methods: Efficacy and safety in METEOR were retrospectively analysed for three age subgroups: <65 (n = 394), 65–74 (n = 201) and ≥75 years (n = 63). Results: PFS, OS and ORR were improved with cabozantinib compared with everolimus in all age subgroups. The PFS hazard ratios (HRs) were 0.53 (95% confidence interval [CI]: 0.41–0.68), 0.53 (95% CI: 0.37–0.77) and 0.38 (95% CI: 0.18–0.79) for <65, 65–74 and ≥75 years, respectively, and the OS HRs were 0.72 (95% CI: 0.54–0.95), 0.66 (95% CI: 0.44–0.99) and 0.57 (95% CI: 0.28–1.14). The ORR for cabozantinib versus everolimus was 15% vs 5%, 21% vs 2% and 19% vs 0%, respectively. No significant differences were observed in PFS or OS with age as a categorical or continuous variable. Grade III/IV adverse events (AEs) were generally consistent across subgroups, although fatigue, hypertension and hyponatraemia occurred more frequently in older patients treated with cabozantinib. Dose reductions to manage AEs were more frequent in patients receiving cabozantinib than in those receiving everolimus. Dose reductions and treatment discontinuation due to AEs were more frequent in older patients in both treatment groups. Conclusions: Cabozantinib improved PFS, OS and ORR compared with everolimus in previously treated patients with advanced RCC, irrespective of age group, supporting use in all age categories. Proactive dose modification and supportive care may help to mitigate AEs in older patients while maintaining efficacy. Highlights: Outcomes by age for cabozantinib vs everolimus were evaluated in previously treated advanced RCC. Cabozantinib improved efficacy outcomes irrespective of age category. Dose reductions due to adverse events were more frequent in older patients. Older patients may benefit from proactive dose modification and supportive care. The results support use of cabozantinib for advanced RCC in all age subgroups.